Simulation and experimental study on the airflow distribution in rectangular cross-section tunnels. Issue 5 (February 2020) - Ding, Cui; Meng, Yanhua
Abstract: Ventilation is quite important for mine safety. The airflow behavior and the influence of the ventilation parameters on the airflow distribution in rectangular tunnels were investigated by experimental and simulation methods. Then the relationship between the distribution feature of the average velocity and the parameters of tunnel cross-section was analyzed quantitatively by mathematical method. The results showed that the average velocity points show a continuous circular distribution and the simulation results were in accordance with the experimental results. The shape of cross-section is the critical factor influencing airflow behaviour, and the ventilation velocity had little influence on the distribution of the average velocity points. In the region where the velocity was larger than the average velocity, the velocity gradient was small, and as the distance to the wall increased, the velocity increased slowly. While in the region where the velocity was smaller than the average velocity, the velocity gradient was large, and the velocity changed more quickly. Based on the simulation and experimental data, a group of the characteristic equations were developed and the location of the average velocity can be obtained conveniently while the dimension of the tunnel was known.